MACROECONOMICS AFTER COVID-19 PANDEMIC - V. Jituri, Vishwajeet (International Journal of Research -GRANTHAALAYAH, 2020)
Macroeconomics concerns with total income, employment, investment etc. at countries level. The modern economy follows 4-sector model; wherein there is engagement of household sector, firms sector, government sector and the foreign sector. The volume of exports and imports of a country in percentage of its GDP gives indication of their exposure to the foreign sector. Post Covid-19, there is tendency of many countries to follow 3-sector economic model and reduce their dependency on the foreign sector. This paper does overview of the economic models in view of the pandemic Covid-19.